The EU Referendum and Experiences and Fear of Ethnic and Racial Harassment: Variation Across Individuals and Communities in England - Nandi, Alita; Luthra, Renee Reichl (Frontiers in Sociology, 2021)
This paper uses nationally representative, longitudinal data to examine experiences and fear of ethnic and racial harassment in public spaces among minorities in the UK, comparing levels of both before and after the 2016 EU Referendum. We do not find an increase in the prevalence of ethnic and racial harassment, but we do find higher levels of fear of ethnic and racial harassment in the period after the Referendum. The increase in fear following the vote was concentrated among more privileged individuals: those with higher levels of education, and those living in less socioeconomically deprived areas with lower levels of previous right-wing party support. We conclude that the Referendum exacerbated already higher levels of perceived discrimination among higher educated minorities while reducing the buffering effect of residence in “safe areas.”